Development of Contemporary Islamic Law - Randi Hermawan; Rabiul Awaluddin (Marga: Journal Of Innovation and Creatifity, 2024)
A concise and concise summary is required (maximum 250 words). The summary should briefly indicate the purpose of the study, the material method, its main results and its major results. The summary is often presented separately from the article, so you need to be able to stand alone. For this reason references should not be used. Times New Roman; 10 pt. Shortly after the summary, provide up to 4-6 keywords avoiding general and plural terms and multiple concepts (eg "and" "). Protected with abbreviations: Strictly used abbreviations may be appropriate. A concise and concise summary is required (maximum 250 words). The summary should briefly indicate the purpose of the study, the material method, its main results and its major results. The summary is often presented separately from the article, so you need to be able to stand alone. For this reason references should not be used. Times New Roman; 10 pt. Shortly after the summary, provide up to 4-6 keywords avoiding general and plural terms and multiple concepts (eg "and" "). Protected with abbreviations: Strictly used abbreviations may be appropriate. A concise and concise summary is required (maximum250 words). The summary should briefly indicate the purpose of the study, the material method, its main results and its major results. The summary is often presented separately from the article, so you need to be able to stand alone. Times New Roman; 10 pt. Shortly after the summary, provide up to 4-6 keywords avoiding general and plural terms and multiple concepts (eg "and" ").